Designing An Integrated Reporting Guidance: An Initiative To Improve Environmental And Social Reporting Quality / Diseño de una guía de informes integrados: una iniciativa para mejorar la calidad de los informes ambientales y sociales - PRATAMA, A.; YADIATI, W.; DEWI TANZIL, N.; SUPRIJADI, J. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Environment and social reporting need to be done in a comprehensively way. Integrated reporting provided opportunities to integrate social and environmental aspects with traditional financial reporting. This research trys to add a new improvement in scoring integrated reporting. A new scoring system consisted of 39 indicators derived from integrated reporting components. This system also provides scoring ranging from none to excellent. This scoring system might be used in the future by companies, auditors, or regulators in conjunction with assessing the quality of the integrated report.RESUMEN El medio ambiente y los informes sociales deben realizarse de manera integral. Los informes integrados brindaron oportunidades para relacionar aspectos sociales y ambientales con los informes financieros tradicionales. Esta investigación trató de agregar una nueva mejora en la calificación de informes integrados. Un nuevo sistema de puntuación consistió en 39 indicadores derivados de componentes integrados de informes. Este sistema también proporciona puntajes que van desde ninguno hasta excelente. Este sistema de puntuación podría ser utilizado en el futuro por compañías, auditores o reguladores junto con la evaluación de la calidad del informe integrado.